2009
DOI: 10.1089/lap.2008.0245
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Revision of Failed Fundoplication and Hiatal Herniorraphy

Abstract: Objective: The aim of this study was to evaluate the mechanisms of failure after laparoscopic fundoplication and the results of revision laparoscopic fundoplication. Background: Laparoscopic Nissen fundoplication has become the most commonly performed antireflux procedure for the treatment of gastroesophageal reflux disease, with success rates from 90 to 95%. Persistent or new symptoms often warrant endoscopic and radiographic studies to find the cause of surgical failure. In experienced hands, reoperative ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
1
20
0
5
Order By: Relevance
“…These results are consistent with prior studies, which demonstrated postoperative resolution or improvement of typical symptoms [8,15,[18][19][20]. Study results showed excellent symptom resolution following both primary and reoperative paraesophageal herniorrhaphy, as evidenced by significant reductions in all composite and individual esophageal and extraesophageal symptom scores in the follow-up period when compared with preoperative scores.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with prior studies, which demonstrated postoperative resolution or improvement of typical symptoms [8,15,[18][19][20]. Study results showed excellent symptom resolution following both primary and reoperative paraesophageal herniorrhaphy, as evidenced by significant reductions in all composite and individual esophageal and extraesophageal symptom scores in the follow-up period when compared with preoperative scores.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have examined symptom resolution with reoperative paraesophageal herniorrhaphy [1,11,12,14,15,17], but a comprehensive evaluation of symptoms in both primary and reoperative paraesophageal herniorrhaphy has not been performed. This study was a retrospective analysis of symptom resolution following reoperative paraesophageal herniorrhaphy and examined the clinical benefit and efficacy of reoperative paraesophageal herniorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the inclusion and exclusion criteria using information available in the published abstracts left 35 articles for a full review. From this pool, the final 17 articles were selected [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. An additional review of the references in these final 17 articles yielded no additional publications for inclusion in the analysis.…”
Section: Search Yieldmentioning
confidence: 99%
“…Well-positioned valves, without evidences of structural defects, can be adequately treated with endoscopic dilation as a first choice; nonetheless, patients with twisted, migrated or anatomically disrupted fundoplications rarely respond satisfactorily to endoscopic treatment and should be taken to early surgical correction (5) . It is worth noting that although some studies have reported satisfactory results after revisional laparoscopic fundoplication (11,25) redo fundoplications usually have worse results than primary surgery (12,23) . For the Nissen LTF, we realize an extensive mobilization of the gastric fundus, with opening and dissection of the The ANOVA and the Equality of Two Proportions Tests were used for statistical analysis of quantitative and qualitative data, respectively.…”
Section: Discussionmentioning
confidence: 99%